Prevalence of risk factors associated with hypertension at Sanglah General Hospital, Bali - Mahen Isaac Pannir Chelvam; I Wayan Sugiritama; I Gusti Nyoman Kamasan Arijana (DiscoverSys Inc., 2020)
Background: High blood pressure, also called